Status of mandatory treatment of mentally ill offenders without criminal responsibility in China: Information from 5,262 mandatory treatment judgments - Qiu, Yu-Feng; Yin, Xiao-Tong; Wang, Zi-Ye; Yang, Rui; Coid, Jeremy; Chen, Xia-Can; Hu, Jun-Mei (Frontiers in Psychiatry, 2023)
Background: To avoid public health risks, all governments ensure monitoring and treatment of mentally ill persons if they offend and assess their level of criminal responsibility. The Criminal Procedure Law of the People's Republic of China (2013) instituted special procedures. However, there are few articles in English which explain the implementation of mandatory treatment procedures in China. Methods: We collected 5,262 qualified documents from 2013 to 2021 from the China Judgments Documents Online. We analyzed social demographic characteristics, trial-related information as well as the mandatory treatment-related content, to investigate the mandatory treatment of China's mentally ill offenders without criminal responsibility, from 2013 to 2021. Simple descriptive statistics and chi-square tests were used to compare differences among several types of documents. Results: There was an overall change trend of the number of documents: increasing year by year from 2013 to 2019 after the implementation of the new law, but with sharp decrease in 2020 and 2021 during covid-19 pandemic. From 2013-2021, a total of 3,854 people had applications made for mandatory treatment, of whom 3,747 (97.2%) were given mandatory treatment, 107 (2.8%) had applications rejected. "Schizophrenia and other psychotic disorders" was the most common diagnosis in both groups and all offenders receiving mandatory treatment (3,747, 100.0%) were considered to have no criminal responsibility. A total of 1,294 patients had applications made for relief of mandatory treatment, of whom 827 (63.9%) were subsequently approved for relief, 467 (36.1%) were rejected. A total of 118 patients had applications for relief two or more times, and 56 (47.5%) were finally relieved. Conclusion: Our study presents the Chinese model of a criminal mandatory treatment system to the international community which has been in operation since the implementation of the new law. Legislatory changes and covid-19 pandemic can have effect on the number of mandatory treatment cases. Patients, their close relatives and mandatory treatment institutions have the right to apply for relief from mandatory treatment, but the final decision in China is taken by the court.